ANALISIS LAPORAN ARUS KAS UNTUK MENILAI KINERJA KEUANGAN PADA PT. INDOFOOD SUKSES MAKMUR TBK TAHUN 2018-2022 - Ikayanti Puspaning Kartini; Umar Hi Salim; Marisa Setiawan (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2025)
The purpose of writing this thesis is to determine the financial performance of PT. Indofood Sukses Makmur Tbk in 2018-2022 based on cash flow ratio.The analytical tools used in this research are the cash flow liquidity ratio in the form of the Operating Cash Flow Ratio (AKO), Fund Flow Coverage Ratio (CAD), Cash Coverage to Interest Ratio (CKB), Cash Coverage to Current Debt Ratio (CKUL), Expenditure Ratio Capital (PM), Total Debt Ratio (TU) and Cash Flow Flexibility Ratio in the form of the Free Net Cash Flow Ratio (AKBB) and Cash Flow Adequacy Ratio (KAK).Based on the results of the discussion that has been described, it can be seen the financial performance of PT. Indofood Sukses Makmur Tbk in 2018-2022 was reviewed from the Operating Cash Flow Ratio (AKO), Cash Coverage to Current Debt Ratio (CKUL), Total Debt Ratio (TU), Free Net Cash Flow Ratio (AKBB) and Cash Flow Adequacy Ratio ( KAK) was declared unfavorable. Meanwhile, in terms of the Funds Flow Coverage Ratio (CAD), Cash to Interest Coverage Ratio (CKB), and Capital Expenditure Ratio (PM) it is stated to be good.